Methods to estimate collision risk and behavioural responses of seabirds around wind turbines in the Firth of Forth - Repas-Goncalves, Miguel; Pina, Luis; Barton, Collin; Cardia, Pedro; Oliveira, Ricardo; Perrow, Martin; Segurado, Pedro; Tarrant, Polly; Machado, Rui; May, Roel (Zenodo, 2023)
The development of wind energy is crucial for mitigating the impacts of climate change. Offshore wind farms are an increasingly used source of renewable energy but there are concerns of their potential effects on wildlife, particularly on seabirds. To address this issue, a comprehensive study has been devised to monitor the impact of the Neart na Gaoithe offshore wind farm, off the east coast of Scotland on two seabird species: northern gannet and black-legged kittiwake. The study will be conducted over a two-year period and will provide a detailed understanding of how these species interact with wind turbines and how they adapt to the changing environment. It will focus on acquiring empirical measures of collision rates and collision risk (micro-avoidance), as well as obtaining three-dimensional records of flight behaviour around wind turbines and the area surrounding the windfarm, to characterize meso- and macro-avoidance responses. A setup comprising three dual radar sets (horizontal and vertical radars), each complemented with two long-range cameras, and six video collision detection systems will be used to monitor the flight patterns of seabirds in the study area, and to detect bird collisions. This technological approach is combined with a strong component of human validation ex situ (for recorded media) and in situ (observers). The use of multiple monitoring systems aims to increase the accuracy and reliability of the data collected, allowing for a more comprehensive assessment of the behavioural responses of the target species. Data obtained from radar will provide estimates of the flux of birds crossing the wind farm to calculate species specific avoidance metrics. The influence of different variables on collision rates will be analysed using a time series approach based on Generalized Additive Modelling. Different models will be fitted considering collision rates estimated for different time resolutions to assess the potential effect of variables acting at different temporal scales. The methodology ...